1986
DOI: 10.1159/000124518
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Aging on Molecular Forms of Beta- and Gamma-Endorphins in Rat Hypothalamus

Abstract: The influence of aging on the molecular forms of endorphins in the hypothalamus of rats was investigated. Extracts of individual hypothalami from 8- and 24-month-old male Fischer 344 rats were subjected to high-performance liquid chromatography. Eluate fractions were assayed for β-endorphin-like immunoreactivity (βE-LI) and γ-endorphin-like immunoreactivity (γE-LI). Hypothalami from adult (8-month-old) rats contained predominantly β-endorphin-1–31 with smaller amounts of β-endorphin-1–27 and 1–26. Only 5% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…The HPLC analyses support previous suggestions that there are age-related alterations in the posttranslational processing of opioid precursors [24], Changes in the proces sing of the DYN precursor molecule have been shown in the HT of developing rats [21], In their study, Seizinger et al [21] found that DYN immunoreactivity in 3-day-old rat pups was represented by larger forms than DYN 1-17. In their 'adult' rats (rats weighing 200-220 g or ~70 days old) the larger forms and DYN 1-17 represented about equal amounts of the immunoreactivity.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The HPLC analyses support previous suggestions that there are age-related alterations in the posttranslational processing of opioid precursors [24], Changes in the proces sing of the DYN precursor molecule have been shown in the HT of developing rats [21], In their study, Seizinger et al [21] found that DYN immunoreactivity in 3-day-old rat pups was represented by larger forms than DYN 1-17. In their 'adult' rats (rats weighing 200-220 g or ~70 days old) the larger forms and DYN 1-17 represented about equal amounts of the immunoreactivity.…”
Section: Discussionsupporting
confidence: 81%
“…A previous study [24] however, does not support this possibility, though it does support the contention that there are increased relative amounts of acetylated forms in the hypothalamus. The authors found HPLC profiles of ir-(IEP and ir-NacEP to be highly variable in hypothalamic ex tracts from senescent animals; overall, however, the mean proportion of acetylated to nonacetylated forms was greater in the old animals.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Consistently, studies carried out in the rat have dem onstrated age-induced changes in [1-endorphin content in the hypothalamus, in the pituitary and plasma [34][35][36], as well as in p-receptor number and in the molecular form of (1-and y-endorphins in the hypothalamus of aged rats [37,38], Accordingly, the present and some other studies have shown that naloxone is unable to modify plasma LH levels in aged male rats [21] and in elderly humans of ei ther sex [39,40].…”
Section: Discussionsupporting
confidence: 53%
“…Changes in the processing of hypothalamic POMC have also been reported to occur in middle-aged female mice [53]as well as in old rats [54], suggesting that ontogenetic changes in the processing of brain POMC occur throughout the life-span. Alterations in POMC processing could occur via changes in the processing enzymes.…”
Section: Discussionmentioning
confidence: 99%